Development of Pedagogical Creativity in Students of Higher Technical Educational Establishments - Mykhailiuk, Iryna; Vavryk, Tetiana (Pedagogical Discourse, 2013)
The article focuses on the formation of pedagogical creativity in students of higher technical educational establishments as a constituent of component of readiness for the professional pedagogical activity. It deals with the growth and development of professional pedagogical aptitudes of the future technically educated lecturer personality. The ways and methods of incentives and promotion of the professional pedagogical activities considering the drawbacks being in the process of creative specialist formation have been offered. The basic ways of shaping the pedagogical creativity in the educational process of higher technical educational establishment have been given.